Enhanced thermoelectric performance of MnTe by decoupling of electrical and thermal transports - Basit, Abdul (2024)
Lead-free polycrystalline manganese telluride holds great potential in the development of waste heat recovery due to its fascinating physical properties. However, the poor thermoelectric (TE) performance in the p-type MnTe alloys always results from their inferior carrier concentration, leading to low power factor and high thermal conductivity which restrict the overall thermoelectric performance. In this work, the problem is solved by decoupling its electrical and thermal transports through the hole donor Ge-deficiency in MnTe + x mol.% GeTe (0 ≤ x ≤ 4) compounds. Intrinsically, extra GeTe in MnTe + x mol.% GeTe compound offers free charge carriers due to a narrow bandgap comparatively, realizing not only a full assessment of stimulated electrical performance but also an enhanced power factor. Moreover, benefiting from the nano-precipitates and tweed microstructures, the lattice thermal conductivity effectively reduces due to the intensive phonon scattering accordingly. Ultimately, a maximum ZT of ≈1.2 at 873 K in the 3 mol.% GeTe doped MnTe sample is realized.